A critical perspective on the transformative capacity of food justice. Issue 11 (2nd November 2018) - Moragues-Faus, Ana
ABSTRACT: As the concept of food justice travels and morphs through its engagement with new geographies, practices and worldviews a key question emerges: what is the transformative capacity of food justice, if any? That is, what are the conditions and agencies that actually confer transformative capacity to food justice as a movement, a narrative, a framework, an outcome or a vision? And, how can academics contribute to unpack (or hinder) this transformative capacity? In his paper I contend that the concept of justice offers a different entry point from well-worn terms such as sustainability and food security by positioning the need to address inequalities' root causes at the forefront of a transformative food agenda. However, if we aim to nurture this potential transformative capacity of food justice, it is paramount to acknowledge its place-based character, relationality and inherently political character.